Figures of Brahma, Vishnu and Shiva on the doorframe of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The lalatbimba (lintel) of the doorframe is relatively plain, featuring three large panels placed at the centre and two on the extreme ends depicting the trinity—Shiva, Vishnu, and Brahma. In the central panel, an ethereal sculpture of Shiva in the form of Nataraja is carved. To the proper left, a sculpture of Vishnu is carved, while to the proper right, a sculpture of Brahma is represented. Nataraja had multiple arms, now all broken, with an elegant posture and glorious face drawing attention. He is accompanied by two musicians who are playing musical instruments. The charming figure of Vishnu is shown holding shankha (conch), gada (mace) and chakra (discuss). The three-faced Brahma is also carved with four arms, now broken, with his vahana (vehicle or mount) at the bottom.